1990
DOI: 10.1109/59.99398
|View full text |Cite
|
Sign up to set email alerts
|

A highly parallel method for transient stability analysis

Abstract: In this paper, a new method for transient stability simulation is presented. The objective of this work is to exploit the maximum degree of parallelism that the problem presents. The transient stability problem can be seen as a coupled set of nonlinear algebraic and differential equations; by applying a discretization method such as the trapezoidal rule, the overall algebraicdifferential set of equations is transformed into an unique algebraic problem a t each time step. A solution that considers every time st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Parallel-in-time simulation strategies have been reported in [5,12,13,20]. Similar to space partitioning, these relaxation (e.g., Gauss-Jacobi) methods allow the time horizon to be partitioned and solved concurrently by dropping the coupling terms in the Newton system between neighboring times steps.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel-in-time simulation strategies have been reported in [5,12,13,20]. Similar to space partitioning, these relaxation (e.g., Gauss-Jacobi) methods allow the time horizon to be partitioned and solved concurrently by dropping the coupling terms in the Newton system between neighboring times steps.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review on iterative methods and power systems problems revealed a majority of steady-state studies [3][4][5][6][7][8][9][10][11][12][13][14][15]. Despite time domain simulation be an important tool for dynamic assessment of power systems [16][17][18], the application of iterative methods have been focused only on the solution of short-term phenomena (transient stability) through implicit integration methods with fixed step sizes, taking advantage of parallel or distributed computing [3,4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Despite time domain simulation be an important tool for dynamic assessment of power systems [16][17][18], the application of iterative methods have been focused only on the solution of short-term phenomena (transient stability) through implicit integration methods with fixed step sizes, taking advantage of parallel or distributed computing [3,4,13,14]. Besides, the reasons for the lower number of references related to time-domain analyses may be associated to the high computational cost when solving complex Differential Algebraic Equations (DAEs) due to the slow or non-convergence presented by earlier unpreconditioned iterative methods, or even by the use of low quality preconditioners.…”
Section: Introductionmentioning
confidence: 99%
“…The basic idea of using simultaneous implicit method using trapezoidal integration method for parallel processing is due to Alvarado [l]. He proposed Newton's method to solve the algebraic equations while LaScala et a1 [2] use the relaxation method on a hypothetical computer. We modify Alvarado's method in two respects (i) consider a detailed multi-machine system resulting in algebraic differential equations and (ii) use the supercomputer Cray 2 with multiple processors.…”
Section: Introductionmentioning
confidence: 99%